Enzymatic hydrolysis of corn stover lignin by laccase, lignin peroxidase, and manganese peroxidase. (October 2022) - Zhang, Sitong; Dong, Zijian; Shi, Jia; Yang, Chengrui; Fang, Yi; Chen, Guang; Chen, Huan; Tian, Chunjie
Graphical abstract: Highlights: Lignin with a relatively complete structure was obtained from corn stover. Using Lac to start enzyme reactions can synergize with LiP and MnP to degrade lignin. A combination of all three enzymes provided the best percentage degradation. Acid compounds dominated the products of enzymatic lignin degradation. Degradative enzymes break key bonds in lignin and open benzene rings. Abstract: Lignin of high purity and structural integrity was isolated from the enzymatic residue of corn stover. Degradation of the lignin by laccase, lignin peroxidase, and manganese peroxidase was investigated. Structural changes in the lignin after degradation were characterized by scanning electron microscopy, nitrogen adsorption and Fourier transform infrared spectroscopy, and the enzymatic products were systematically analyzed by gas chromatography mass spectrometry. The highest percentage of lignin degradation was obtained with a mixture of three enzymes (25.79%): laccase (Lac), the starting enzyme of the mixed enzyme reaction, worked with lignin peroxidase (LiP), and manganese peroxidase (MnP) to further degrade lignin. This degradation destroyed the macromolecular structure of lignin, broke its key chemical bonds, and opened benzene rings, thus producing more acidic compounds. This study elucidated the concept of degrading lignin from corn stover using the Lac, LiP and MnP enzymes synergistically, thus providing a theoretical basis for the biodegradation of lignin.